Oligodendrocyte precursor cell-derived exosomes combined with cell therapy promote clinical recovery by immunomodulation and gliosis attenuation - Santos, Sarah Ingrid Pinto; Ortiz-Peñuela, Santiago José; de Paula Filho, Alessandro; Tomiyama, Ana Laura Midori Rossi; Coser, Lilian de Oliveira; da Silveira, Juliano Coelho; Martins, Daniele dos Santos; Ciena, Adriano Polican; de Oliveira, Alexandre Leite Rodrigues; Ambrósio, Carlos Eduardo (Frontiers in Cellular Neuroscience, 2024)
Multiple sclerosis is a chronic inflammatory disease of the central nervous system characterized by autoimmune destruction of the myelin sheath, leading to irreversible and progressive functional deficits in patients. Pre-clinical studies involving the use of neural stem cells (NSCs) have already demonstrated their potential in neuronal regeneration and remyelination. However, the exclusive application of cell therapy has not proved sufficient to achieve satisfactory therapeutic levels. Recognizing these limitations, there is a need to combine cell therapy with other adjuvant protocols. In this context, extracellular vesicles (EVs) can contribute to intercellular communication, stimulating the production of proteins and lipids associated with remyelination and providing trophic support to axons. This study aimed to evaluate the therapeutic efficacy of the combination of NSCs and EVs derived from oligodendrocyte precursor cells (OPCs) in an animal model of multiple sclerosis. OPCs were differentiated from NSCs and had their identity confirmed by gene expression analysis and immunocytochemistry. Exosomes were isolated by differential ultracentrifugation and characterized by Western, transmission electron microscopy and nanoparticle tracking analysis. Experimental therapy of C57BL/6 mice induced with experimental autoimmune encephalomyelitis (EAE) were grouped in control, treated with NSCs, treated with OPC-derived EVs and treated with a combination of both. The treatments were evaluated clinically using scores and body weight, microscopically using immunohistochemistry and immunological profile by flow cytometry. The animals showed significant clinical improvement and weight gain with the treatments. However, only the treatments involving EVs led to immune modulation, changing the profile from Th1 to Th2 lymphocytes. 15 days after treatment revealed a reduction in reactive microgliosis and astrogliosis in the groups treated with EVs. However, there was no reduction in demyelination. The results indicate the potential therapeutic use of OPC-derived EVs to attenuate inflammation and promote recovery in EAE, especially when combined with cell therapy.